Determination of Hepatitis A Virus, Enterobacteriaceae, Coliform and Escherichia coli Contamination of Frozen Raspberries - İncili, Gökhan Kürşad; Koluman, Ahmet; Dikici, Abdullah (My University, 2019)
Hepatitis A is transferred via fecal-oral route, direct contact from person to person or with ingestion of contaminated food. Foods like, raspberries, strawberries and blueberries are important source of hepatitis A virus (HAV). Frozen retail packaged raspberries are analyzed in this study. Frozen raspberry samples have were obtained from local supermarkets monthly between January and December 2015 in Ankara province, Turkey. The samples were evaluated for HAV contamination using ISO/TS 15216-1:2013 in duplicate and Mengovirus was used for process control. Samples that found to be contaminated with HAV were further analyzed for Enterobacteriaceae Coliform and Escherichia coli. Totally 240 samples were analyzed and 20 (8.33%) were found to be contaminated with HAV. The highest HAV prevalence was on 6th month (25%). On the contrary no HAV was found on 3rd, 4th and 10th months of analyzes. The highest Enterobacteriaceae, Coliform and E. coli counts were found on 2nd month 4.90, 4.84 and, 3.48 log10 cfu/g, respectively. The results indicate that even the food relies with the microbiological criteria, there is no guarantee for viral contamination. Additionally, high cost of virus analyzes is another barrier for routine control which has a direct impact on public health. Additional measures like HACCP, GHP and GMP should be applied strictly from farm to fork to avoid contamination with HAV.
Keywords: Halk ve Çevre Sağlığı; Mikrobiyoloji; Gıda Bilimi ve Teknolojisi